Analisis Kuantitatif Dokumen Rekam Medis Rawat Inap di Rumah Sakit Ibnu Sina Kabupaten Gresik - Yuliani, Resta Dwi (Jurnal Informasi Kesehatan Indonesia (JIKI), 2023)
Medical records are data for compiling health information for both outpatient and inpatient visits. Based on the Minister of Health's decision number 129 of 2008 concerning minimum hospital service standards, recording medical record documents must be 100% complete and correct. The aim of this research is to analyze the incompleteness of inpatient medical records at Ibnu Sina Hospital, Gresik Regency based on 4 aspects, namely, the social data identification aspect, the important report aspect, the authentication aspect, and the correct documentation aspect. The population in this study is the number of inpatient medical record documents that have been deposited for the period June and July 2023, amounting to 1400 sample files obtained using random sampling techniques. Determining the sample size using the Slovin formula resulted in 100 medical record documents. This research is descriptive quantitative research. Based on the results of the analysis, identification reviews were on average complete 51%, incomplete 49%, reviews of important reports were on average complete 82.83%, incomplete 61%, authentication reviews were on average complete 66%, incomplete 34%, and On average, the correct documentation review was 61% complete, 31% incomplete. There needs to be outreach about the importance of patient identification to registration officers and all patient care providers. As well as the formation of a medical records committee and activeness of the room in monitoring the completeness of medical records Keywords: Authentication review, correct documentation review, identification review, important report review